Factors influencing implementation of an insulin patient decision aid at public health clinics in Malaysia: a qualitative study - Wen, Ting Tong; Yew, Kong Lee; Chirk, Jenn Ng; Ping, Yein Lee (Public Library of Science, 2020)
Background: Many patient decision aids (PDAs) are developed in academic settings by academic researchers. Academic settings are different from public health clinics where the focus is on clinical work. Thus, research on implementation in public health settings will provide insights to effective implementation of PDA in real-world settings. This study explores perceived factors influencing implementation of an insulin PDA in five public health clinics. Methods: This study adopted a comparative case study design with a qualitative focus to identify similarities and differences of the potential barriers and facilitators to implementing the insulin PDA across different sites. Focus groups and individual interviews were conducted with 28 healthcare providers and 15 patients from five public health clinics under the Ministry of Health in Malaysia. The interviews were transcribed verbatim and analysed using the thematic approach. Results: Five themes emerged which were: 1) time constraint; 2) PDA costs; 3) tailoring PDA use to patient profile; 4) patient decisional role; and 5) leadership and staff motivation. Based on the interviews and drawing on observations and interview reflection notes, time constraint emerged as the common prominent factor that cut across all the clinics, however, tailoring PDA use to patient profile; patient decisional role; leadership and staff motivation varied due to the distinct challenges faced by specific clinics. Among clinics from semi-urban areas with more patients from limited education and lower socio-economic status, patients’ ability to comprehend the insulin PDA and their tendency to rely on their doctors and family to make health decisions were felt to be a prominent barrier to the insulin PDA implementation. Staff motivation appeared to be stronger in most of the clinics where specific time was allocated to diabetes team to attend to diabetes patients and this was felt could be a potential facilitator, however, a lack of leadership might affect the insulin PDA implementation even though a diabetes team is present. Conclusions: This study found time constraint as a major potential barrier for PDA implementation and effective implementation of the insulin PDA across different public health clinics would depend on leadership and staff motivation and, the need to tailor PDA use to patient profile. To ensure successful implementation, implementers should avoid a ‘one size fits all’ approach when implementing health innovations.